La Biennale di Venezia : XXIX Biennale internazionale d'arte 1958. - La Biennale di Venezia, XXIX Biennale internazionale d'arte, 1958 (Venezia : La biennale di Venezia, 1958)
Kenneth Armitage ; Enrico Baj ; Julius Bissier ; Georges Braque ; Jean Brusselmans ; Alberto Burri ; Eduardo Chillida ; Alan Davie ; Piero Dorazio ; Amedeo Fiorese ; Lucio Fontana ; Nino Franchina ; Johnny Friedlaender ; Franco Gentilini ; Werner Gilles ; Karl Otto Götz ; Marcello Grassmann ; Otto Herbert Hajek ; Jasper Johns ; Wassily Kandinsky ; Gustav Klimt ; Fritz Koenig ; Alfred Manessier ; André Masson ; Mario Negri ; Palle Nielsen ; Kenzo Okada ; Fayga Ostrower ; Otto Pankok ; Antoine Pevsner ; Hans Platschek ; Mario Radice ; Germaine Richier ; Mark Rothko ; Karl Schmidt-Rottluff ; Johanna Schütz-Wolff ; Emil Schumacher ; William Scott ; Lasar Segall ; David Smith ; K.R.H. Sonderborg ; Luigi Spacal ; Richard Stankiewicz ; Jacob Steinhardt ; Gabrijel Stupica ; Antoni Tàpies ; Fred Thieler ; Mark Tobey ; Heinz Trökes ; Alberto Viani ; Wilhelm Wessel ; Hans Wimmer ; Wols , Ernst Zmetak
La Biennale di Venezia, XXiX Biennale internazionale d'arte, 14.06 - 30.10.1958
Italiaans
kunstcatalogus